2010
DOI: 10.4141/cjas09107
|View full text |Cite
|
Sign up to set email alerts
|

The influence of supplementation with haylage, haylage plus soybean meal or haylage plus corn dried distillers’ grains with solubles on the performance of wintering pregnant beef cows fed wheat straw

Abstract: Wood, K. M., Mandell, I. B. and Swanson, K. C. 2010. The influence of supplementation with haylage, haylage plus soybean meal or haylage plus corn dried distillers' grains with solubles on the performance of wintering pregnant beef cows fed wheat straw. Can. J. Anim. Sci. 90: 547Á553. Fourteen pens containing a total of 53 individually fed, multiparous, pregnant, crossbred beef cows were used to investigate feeding of free-choice haylage or supplemention programs for cows fed wheat straw. Dietary treatments fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Although dam BW changes were observed due to treatment, calf birth weights were not impacted by main treatment effects or their interactions. This result is supported by multiple studies that found that protein supplementation during pregnancy did not influence calf birth weights (Wilson et al, 2016;Stalker et al, 2014;Warner et al, 2011;Wood et al, 2010). Studies that found dam nutrition influenced calf birth weights primarily involved severe energy restriction during gestation (Taylor et al, 2016 andGao et al, 2012).…”
Section: Cow Performancementioning
confidence: 76%
“…Although dam BW changes were observed due to treatment, calf birth weights were not impacted by main treatment effects or their interactions. This result is supported by multiple studies that found that protein supplementation during pregnancy did not influence calf birth weights (Wilson et al, 2016;Stalker et al, 2014;Warner et al, 2011;Wood et al, 2010). Studies that found dam nutrition influenced calf birth weights primarily involved severe energy restriction during gestation (Taylor et al, 2016 andGao et al, 2012).…”
Section: Cow Performancementioning
confidence: 76%
“…Although diagnosis of a disease can only be done based on the total number of complete red blood cells (CBCs), measurement of blood cells in the patient may provide valuable information for diagnosis (Roland, Drillich, & Iwersen, 2014). As with other species, a certain amount of physiological variability is observed in the hematological profile of the cattle, which depends on the age, sex, stress, ration, body condition score, production conditions, and animal activity (Wood, Mandell, & Swanson, 2010). White blood cells or leukocytes have an essential role in the immune system, and include subgroups of different neutrophils, eosinophils, granulocytes, monocytes and lymphocytes.…”
Section: Hematological Blood Parametersmentioning
confidence: 99%